2011
DOI: 10.1186/1471-2458-11-311
|View full text |Cite
|
Sign up to set email alerts
|

Television viewing, food preferences, and food habits among children: A prospective epidemiological study

Abstract: BackgroundObesity has increased since the early 1980s, and despite numerous attempts, effective strategies to counter this worldwide epidemic are lacking. Food preferences are established early in life and are difficult to change later. There is therefore a need to identify factors that influence the development of food preferences. Our aim was therefore, to investigate cross-sectional and prospective associations between TV viewing habits and food preferences and habits, respectively. We hypothesized that mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
18

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 39 publications
5
59
0
18
Order By: Relevance
“…The relationship between consumption of fruits and vegetables and exposure to sedentary behavior found in males students was similar to other studies such as that conducted with adolescents in Denmark,26 which verified association between unhealthy eating preferences and longer time spent watching television. In Austrália,27 the authors found significant association between TV time equal to or greater than two hours (≥2h/day) and consumption of soft drinks and salty snacks, and an inverse association between TV time (≤2h/day) and consumption of fruits and vegetables.…”
Section: Discussionsupporting
confidence: 88%
“…The relationship between consumption of fruits and vegetables and exposure to sedentary behavior found in males students was similar to other studies such as that conducted with adolescents in Denmark,26 which verified association between unhealthy eating preferences and longer time spent watching television. In Austrália,27 the authors found significant association between TV time equal to or greater than two hours (≥2h/day) and consumption of soft drinks and salty snacks, and an inverse association between TV time (≤2h/day) and consumption of fruits and vegetables.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, extended periods spent watching television has been associated with generally having less healthy food preferences and food habits in school-aged children (36) ; thus these factors may act together in an undesirable direction.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] These trends could possibly result from the displacement of fruit by other frequently advertised foods. Screen viewing time activities, in particular TV viewing, have been associated with unhealthy eating practices 8,40,41 and may partly explain the relationship between sedentary behaviors and obesity. 42 During the past few years, sugar-sweetened beverage consumption emerged as the dietary factor most consistently associated with increasing weight status or fatness and subsequently with the obesity epidemic.…”
Section: Commentmentioning
confidence: 99%